PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HOREY TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 12 PADANG - Sari, Widya Novita; K, Delsi; Harisman, Yulyanti (Pendidikan Matematika, 2013)
This research was conducted based on the fact that the studentsâ understanding on mathematics concepts was still low. The students were less inclined and get bored to be engaged in a group discussion. The aim of this research was to see whether the use of Course Review Horey cooperative learning model gave better effect on the studentsâ understanding on mathematics in class VIII of SMPN 12 Padang. This experimental research applied random design toward the subject. The population of the research was the students in class VIII of SMPN 12 Padang. The instrument used was a post-test whose indicator was conceptual understanding. The data then was analyzed by using one way t-test. After the model applied, the average score of the students in the experimental class was 75,96Â  and the standard deviation was 17,32, and the average score for the control one was 56,34 and the standard deviation was 15,97. The result of the post-test indicated that tcalculated (4,63) > ttable (1,67). Thus, it was concluded thatÂ  the use of Course Review Horey cooperative learning model could improve the studentsâ understanding on mathematics concepts better than that of the conventional one in class VIII of SMPN 12 Padang in Academic Year 2012/2014.